Research Contributions of Present Faculty Members at University of Madras - Muthuraj, A.; Bakkiyaraj, N. (Journal of Data Science, Informetrics, and Citation Studies)
This paper explores the research contributions of present faculty members of University of Madras. The present faculty member’s information was obtained from the University of Madras website, while publication information was obtained from the Web of Science and Scopus databases. This study will also examine the faculty members by department, publications, top 10 faculty members, and projects. It has been discovered that the University of Madras has 18 Schools, 1 department, and 253 faculty members presently working, as well as 2707 research publications published on the Web of Science and 4231 research papers published in the Scopus database. A total of 425 research projects were received by the present faculty members of Madras University. It is also revealed that the Department of Nuclear Physics has contributed the most publications (394 (14.55%) from Web of Science, while the Department of Organic Chemistry has contributed 1112 (26.28%) from Scopus, and that the Department of Inorganic Chemistry has received 29 (6.82%) funding projects.
Keywords: Research Contributions; University of Madras; Publications; Citations; Faculty Profiles.